Digital Employer Engagement and Learning for Hospitality and Tourism under Pandemic and Other Crisis Situation - Liasidou, Sotiroula; Pericleous, Katerina; Neophytou, Raphaella; Christina, Kontogoulidou; Zoi, Katsiris; Christos, Mettouris; Evangelia, Vanezi; Papadopoulos, George; Makrides, Gregory; Yancheva, Krasimira; Niyazieva, Selvet; Batle Lorente, Francisco Julio; et al. (My University, 2024)
The COVID-19 pandemic has profoundly impacted the hospitality and tourism industries, necessitating rapid adaptation to unprecedented challenges. This study explores the role of digital employer engagement and learning in ensuring the resilience and continuity of hospitality and tourism businesses during crises. Additionally, the study examines the integration of digital tools in an electronic platform to maintain academic institution-student engagement, facilitate continuous learning, and upskill the workforce in response to evolving industry demands. The research highlights the analysis of focus groups with tourism industry professionals in Latvia, Cyprus, Greece, Bulgaria, and Spain, with the results providing insight on the creation of an online platform of communication. The platform brings together students, academics, and industry professionals in an interactive approach to managing opportunities for the industry. The focus group formation aimed to gain information mainly on the needs, areas, and forms of collaboration between the HTI and the HEIs through a digital platform. The study's results showcase the development of the DEELforHOST electronic platform (https://deel4host.cs.ucy.ac.cy), emphasise the importance of fostering a closer relationship with the industry, offer a comprehensive understanding of real-life scenarios, and help bridge the gap between theory and practice. Technology has pioneered and revolutionised instant contact and interaction with limited time, catering to a global, multicultural audience. Initiatives for digital employer engagement, like virtual meetings, online training programmes, and digital communication channels, have demonstrated their essential role in maintaining the operational functionality of industry leaders. The implementation of e-learning modules, webinars, and virtual simulations can enable participants to acquire new skills and adapt to the changing landscape of the industry. This research provides valuable insights for industry stakeholders and academics to develop robust strategies incorporating technology that ensure interaction among industry partners for sustainability and growth in an increasingly uncertain world.
Keywords: industry academia cooperation; pandemic; crises; higher education; tourism industry; technology; online platform